2003
DOI: 10.4319/lo.2003.48.4.1419
|View full text |Cite
|
Sign up to set email alerts
|

Deep‐water renewal in Lake Issyk‐Kul driven by differential cooling

Abstract: During two field campaigns on Lake Issyk-Kul in March and August 2001, 179 high-resolution conductivitytemperature-depth profiles were measured, along with profiles of dissolved oxygen and light transmission. On the basis of this extensive data set, we investigated the large-scale vertical advective processes responsible for deepwater renewal in Lake Issyk-Kul. At some locations sampled in March, variable peak structures in the tracer profiles were observed that indicate horizontally localized intrusions. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 18 publications
3
52
0
Order By: Relevance
“…The thickness of the upwelling zone layer in large lakes of the world can vary from 10 to 20 m in Lake Onega (17 m, Boyarinov and Petrov 1991) to several tens of metres in Lake Tanganyika (60-66 m, Corman et al 2010) and up to hundreds of metres in Lake Issyk-Kul (100-200 m, Romanovskiy and Shabunin 1981;Kipfer and Peeters 2002;Peeters et al 2003) and Lake Baikal (300-400 m, present paper). The temperature differences between up-and downwelling zones on the water surface of temperate lakes is similar, varying within 5-8°C in July-September (Romanovskiy and Shabunin 1981, present paper) and decreasing by up to 1-1.5°C in OctoberNovember (Romanovskiy and Shabunin 1981, Fig.…”
Section: Lake Baikalmentioning
confidence: 67%
See 2 more Smart Citations
“…The thickness of the upwelling zone layer in large lakes of the world can vary from 10 to 20 m in Lake Onega (17 m, Boyarinov and Petrov 1991) to several tens of metres in Lake Tanganyika (60-66 m, Corman et al 2010) and up to hundreds of metres in Lake Issyk-Kul (100-200 m, Romanovskiy and Shabunin 1981;Kipfer and Peeters 2002;Peeters et al 2003) and Lake Baikal (300-400 m, present paper). The temperature differences between up-and downwelling zones on the water surface of temperate lakes is similar, varying within 5-8°C in July-September (Romanovskiy and Shabunin 1981, present paper) and decreasing by up to 1-1.5°C in OctoberNovember (Romanovskiy and Shabunin 1981, Fig.…”
Section: Lake Baikalmentioning
confidence: 67%
“…The authors found that upwellings in the pelagic area of the lake lead to an increase in dissolved oxygen in the surface layer Shabunin 1981, 2002) that is inversely distributed during summer stratification (Karmanchuk 2002). Later, in a study of vertical water exchange using temperature, conductivity, pressure, dissolved oxygen and light transmission data, Kipfer and Peeters (2002) and Peeters et al (2003) described upwelling in the upper 200-m layer of the water in the central part of Lake Issyk-Kul. Corman et al (2010) analysed upwellings in Lake Tanganyika induced by longitudinal winds and their influence on changes in water temperature and concentrations of nutrients and phytoplankton.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, 80% of the lake's volume (14,960 km 3 or 459 m averaged over the lake surface) is cooler than 24uC, and 76% is cooler than 23.85uC (potential temperatures). Deep cool water formation is not likely driven by evaporative cooling under current conditions occurring offshore (Peeters et al 2003), but is more likely driven by cooling in shallow inshore areas, where surface cooling is more rapid than offshore (Wells and Sherman 2001), followed by convective downflows along the bottom, starting at the lake margins. Such cooling of the hypolimnion by marginal downflows does not require overturn mixing, although these downflows may entrain larger volumes, and does not disrupt stratification, but instead maintains it.…”
Section: Discussionmentioning
confidence: 99%
“…It is situated at an altitude of 1607 m above sea level and surrounded by high mountain ranges: the Kungey Ala-Too Range in the north with the highest peaks reaching 4770 m, and the Teskey Ala-Too Range in the south with peaks exceeding 5200 m [22][23][24], see in Figure 1. The total area equals approximately 22,080 km 2 , of which the lake occupies 6236 km 2 , the coastal zone called zone dissipation runoff occupies 3092 km 2 , and other part of the basin (12,752 km 2 ) is occupied by mountain areas.…”
Section: Description Of the Study Areamentioning
confidence: 99%